The LCA4CSA framework: Using life cycle assessment to strengthen environmental sustainability analysis of climate smart agriculture options at farm and crop system levels - Acosta-Alba, Ivonne; Chia, Eduardo; Andrieu, Nadine (Elsevier, 2019)
Climate Smart Agriculture (CSA) seeks to meet three challenges: improve the adaptation capacity of agricultural systems to climate change, reduce the greenhouse gas emissions of these systems, and ensure local and global food security. Many CSA assessment methods that consider these three challenges have emerged, but to better assess the environmental resilience of farming systems, other categories of environmental impacts beyond climate change need to be considered. To meet this need, we propose the LCA4CSA method, which was tested in southern Colombia for family farming systems including coffee, cane and small livestock production. This methodological framework is based on Life Cycle Assessment (LCA) and multi-criteria assessment methods. It integrates CSA-related issues through the definition of Principles, Criteria and Indicators, and involves farmers in the assessment of the effects of CSA practices. To reflect the complexity of farming systems, the method proposes a dual level of analysis: the farm and the main cash crop/livestock production system. After creating a typology of the farming systems, the initial situation is compared to the situation after the introduction of a CSA practice. In this case, the practice was the use of compost made from coffee processing residues. The assessment at the crop system level made it possible to quantify the mitigation potential related to the use of compost (between 22 and 41%) by taking into account operations that occur on and upstream of the farm. However, it showed that pollution transfers exist between impact categories, especially between climate change, acidification and terrestrial eutrophication indicators. The assessment made at the farming system level showed that farms with livestock units could further limit their emissions by modifying the feeding of animals due to the large quantities of imported cereals. The mitigation potential of compost was only 3% for these farms. This article demonstrates the merits of using life cycle thinking that can be used to inform stakeholder discussions concerning the implementation of CSA practices and more sustainable agriculture.